Current trend of maternal health in Indonesia (Medical Journal of Indonesia, 2012)
Background: Achievement of Millennium Development Goals (MDGs) will be assessed in the next three years (2015). Several parameters in the area of maternal health are evaluated continuously. The aim of this paper is to formally summarize and report the state of maternal health in Indonesia based on the data from Basic Health Survey (Riskesdas) 2010. Methods: This paper utilizes tertiary data obtained from the latest Riskesdas (2010). Results: Data that is available in the report covers data about marriage, reproduction health, abortion, access to health care for pregnancies, place of labor, health care provider, as well as rate of the first postpartum period visit. Conclusion: The latest data shows improvement in the maternal health area, nevertheless large effort in maintaining and improving the condition is still needed. Continuous evaluation is also proven to be essential in achieving the goals. (Med J Indones. 2012;21:179-83)